Myelopathy in Holstein X Gir Calves in Brazil - Alexandre Secorun Borges; Luiz Cláudio Nogueira Mendes; Maria Cecília Rui Luvizotto; Brian A. Summers; Alexander de Lahunta (2003)
This case report contains clinical and pathologic features of a degenerative myelopathy in Holstein X Gir crossbred calves in Brazil. The bilateral and symmetrical spinal cord white matter lesions were interpreted as a primary axonopathy that may be of the dying-back type.